Police and crime commissioners: the first twelve months. Issue 1 (7th January 2014) - Brain, Timothy
Abstract : Purpose: – The purpose of this paper is to review the establishment of this new type of elected official and the conduct of those in office during the first twelve months of their official existence, and to consider whether a compelling case has yet been made for its retention as the principal method of police governance. Design/methodology/approach: – The paper will review policy papers and data which preceded and followed the establishment of the office of police and crime commissioner (PCC) in November 2012; review the 2012 elections and their implications, review conduct since, particularly in respect of formal duties, principally setting budgets and police and crime plans; consider the potential for politicisation; and consider whether a case has been made for the retention of the office in future. Findings: – The paper concludes that the government has succeeded with PCCs in implementing a major plank of the Conservative party's 2010 manifesto. It can reasonably be anticipated that the Conservatives will promote this record at the next election. However, it is simply too early to tell if PCCs are individually or collectively adding value to the sum of policing in England and Wales. A compelling case for their retention as a means of police governance is therefore yet to be made. On the other hand, Labour has still to determine whether it will offer the electorate an alternative in 2015. Research limitations/implications: – With only ten months having elapsed since the first elections, it is early to draw firm conclusions about the effectiveness or, more pertinently, the added value that PCCs have brought to policing. Conversely, the first twelve months was an opportunity for PCCs to make a positive impression and this has not occurred. Practical implications: – PCCs ought to be subject to a rigorous appraisal of effectiveness. This is unlikely, for political reasons, to occur. Originality/value: – First rigorous review of PCCs based on a review of available data.